Analyse the financing structure of agricultural enterprises in 2002–2006 - Herczeg, Adrienn (Applied Studies in Agribusiness and Commerce, 2009)
The capital structure of agricultural enterprises notable modified since the change in Hungary’s economic system. The study discusses the capital structure of agricultural enterprises in Hungary and analyses the most significant indicators, that we can use to describe the financing situation of the firms. My empirical analysis is based on data containing 192 agricultural enterprises between 2002 and 2006. I try to assess the reasons of the changes in the structure of resources of enterprises in order to find the determinants effecting the capital structure. Furthermore, I assess the index numbers illustrating the management of the enterprises.